Mapping anxiety - Hook, Derek (PINS-Psychology in Society, 2015)
Lacan, Jacques (2014) Anxiety. The seminar of Jacques Lacan: Book X. (Edited by Jacques-Alain Miller, Translated by A R Price.) Cambridge: Polity Press (2004-French). ISBN: 978-0-7456-6041-7 hbk. Pages 352